Evaluation of the Effect of Acrylamide and Furfural on Some Biochemical and Liver Histological Variables in Adult Male Albino Mice: Evaluasi Pengaruh Akrilamida dan Furfural terhadap Beberapa Variabel Biokimia dan Histologi Hati pada Tikus Albino Jantan Dewasa - Maha flyih Hassan; Makarim Mustafa Kamal (Academia Open, 2025)
General Background: The liver plays a critical role in metabolism and detoxification, processing substances such as acrylamide and furfural, which are commonly present in heat-processed foods. Specific Background: Acrylamide, formed during the cooking of starchy foods, is metabolized in the liver to glycidamide, a highly reactive compound. Furfural, found in various heat-processed foods, can also negatively impact liver health. Knowledge Gap: Limited research has investigated the comparative effects of acrylamide and furfural on liver function and histology. Aims: This study aimed to evaluate the biochemical and histological effects of acrylamide and furfural on liver function in adult male albino mice. Results: The results revealed significant alterations in lipid profiles, including increased HDL and VLDL levels, as well as histopathological damage such as hepatocyte hypertrophy, leukocyte infiltration, and necrosis. Elevated liver enzyme levels (ALT, AST, ALP) indicated compromised liver function. Novelty: This study provides novel insights into the comparative toxicity of acrylamide and furfural on liver tissue and function. Implications: The findings suggest that prolonged exposure to acrylamide and furfural may induce oxidative stress and liver disease. Further research is needed to explore protective interventions and inform regulatory policies regarding exposure limits to these compounds. Highlights: Hepatoprotective Effect: Astaxanthin reduces diazinon-induced liver damage in rats. Dose-Dependent: 100 mg/kg astaxanthin shows strongest protective effects. Mechanism: Reduces oxidative stress, inflammation, and liver enzyme levels. Keywords : Acrylamide, liver tissues , Furfural, liver function .